KEY TALENT RETENTION DRIVERS IN DIGITAL START-UPS IN MALAYSIA: THE MEDIATING ROLE OF ORGANISATIONAL COMMITMENT AND PERSON-ORGANISATION FIT - Amy, Yeo Chu-May; Ming, Lim Jay; Carter, Steve (Graduate Program of Universitas Tarumanagara, 2024)
The paucity of research on talent retention in digital start-ups in Malaysia is considerably high. This study, therefore, aims to investigate relevant key antecedents that have affected talent retention, particularly in the context of the ongoing endemic. A hypothetical deductive study, using a survey involving 207 respondents who are employees currently working in digital start-ups in Malaysia. Data obtained were analysed using Statistical Package for the Social Sciences (SPSS) and the Partial Least Squares–Structural Equation Modelling (PLS-SEM). The findings revealed that a supportive work environment was directly affecting talent retention, with career development also affecting indirectly the retention of digital personnel through organisational commitment. However, the findings also indicated that neither career development had no significant effect on talent retention nor person-organisation fit had any mediating effect. The outcomes of the study provide evidence that employees engagement drivers are playing vital roles in affecting the talent retention in digital entrepreneurship. It also serves as a guide for the formulation of human resource strategies on talent development and retention. Thus, Malaysian digital entrepreneurs would be able to gain insights on how to leverage the engagement drivers in order to retain great talents.